Analisis Komparasi Metode Sistem Pendukung Keputusan pada Gaya Belajar “VARK” - Riani, Ambar; Taswanda Taryo; Achmad Hindasyah (Jurnal Ilmiah Informatika Global, 2023)
Learning style is an important factor in the success of the learning process from learning resources to individuals or groups. Understanding learning styles can be a strategy in the learning process. One of the learning styles is "VARK" which is the preference of individuals or learning groups consisting of visual, aural, read/write, and kinesthetic. Various methods are developed to find out the learning style of an individual or group of learners. In this research, a decision support system (SK) will be developed that provides learning style recommendations for individuals or study groups whether the tendency is visual, aural, read/write, or kinesthetic. The method used is a combination of simple additive weighting (SAW) and weighted product (WP).  The SPK development stages consist of data collection through distributing surveys to 55 student respondents at the 1926 Education Foundation where the dominant characteristic of the respondent's learning style is visual, namely 56%, analyzing SAW and WP methods, developing SPK with a web-based system, testing the system using the black box testing method.